Strategi Program Kemandirian Ummat Lazismu Dalam Upaya Pemberdayaan Masayarakat Di Kota Pekanbaru - Muharrani Muharrani; Yeni Yasyah Sinaga; Lailan Rafiqah (LPPM STAI Diniyah Pekanbaru, 2020)
Community empowerment is absolutely necessary to create an independent society so that a good strategy is needed to be able to achieve it, LAZISMU is one of the institutions that strive to create an independent society in the economic sector through the community independence program, which is expected to be a problem solver for people who have difficulty in the economic sector through productive loans which in the end were able to deliver the mustahiks to become muzzaki. This study aims to determine how the LAZISMU community independence program strategy in the community empowerment efforts in the city of Pekanbaru. This research is qualitative narrative research. The research subjects were the director of the implementing agency, c.o in the fields of education and economics, and two mustahik or program beneficiaries. The results showed that the strategies implemented by LAZISMU in the community independence program were providing business capital assistance, providing productive facilities, providing business coaching and mentoring as well as providing entrepreneurial training and motivation. Meanwhile, our hope is that the results of this research can be used by institutions engaged in the same field, both government and private institutions so that in the end it can strengthen the people's economy.